Hepatoprotective Effects of Thespesia lampas Dalz & Gibs in CCl4 Induced Liver Injury in Rats - Sangameswaran, B; Deshraj, Chumbhale; Balakrishnan, BR; Jayakar, B (Dhaka University Journal of Pharmaceutical Sciences, 2008)
<!--[if gte mso 9]> Normal 0 false false false MicrosoftInternetExplorer4 <![endif]--><!--[if gte mso 9]> <![endif]--> <!--[if gte mso 10]> <![endif]--> The extracts of the roots of Thespesia lampas (Malvaceae) were evaluated for hepatoprotective activity in rats by inducing chronic liver damage by subcutaneous injection of 50% v/v carbon tetrachloride in Tween 80 at a dose of 3ml/kg for a period of 4 weeks. The biochemical parameters like serum glutamate pyruvate transaminase (SGPT), serum glutamate oxaloacetate transaminase (SGOT), alkaline phosphatase (ALP), serum bilirubin and total proteins were estimated to assess the liver function. Hepatic steatosis, centrilobular necrosis, and often swelling of the hepatic cytoplasm were observed in carbontetra chloride treated group, while these were completely absent in the extracts of T. lampas (300 mg/kg b.wt) treated groups (p < 0.01). The present investigation established pharmacological evidence to support the folkloric claim of hepatoprotective activity of T. lampas. Key words: Thespesia lampas, Carbon tetrachloride, Hepatoprotective, Rats, Root extracts Â  DOI = 10.3329/dujps.v7i1.1201 Dhaka Univ. J. Pharm. Sci. 7(1): 11-13, 2008 (June)